An update - Canadian non-energy exports: Past performance and future prospects - André Binette; Daniel de Munnik; Julie Melanson (Bank of Canada, 2015)
In light of the fact that Canada was continuing to lose market share in the United States, Binette, de Munnik and Gouin-Bonenfant (2014) studied 31 Canadian non-energy export (NEX) categories to assess their individual performance. From this list, about half were expected to lead the recovery in exports. Since that time, NEX growth has picked up: about 80 per cent of the 31 categories have grown in line with, or outperformed, their respective U.S. benchmarks. Furthermore, about half are currently showing upward momentum. Many export categories highly sensitive to the exchange rate have been a key source of strength, as they benefited from the further depreciation of the Canadian dollar. In addition, a more granular analysis finds that export product categories are emerging or re-emerging from low levels. On the downside, however, some categories closely linked to commodity prices have been affected by weak activity and lower prices. – – Face au recul persistant des parts de marché du Canada aux États-Unis, Binette, de Munnik et Gouin-Bonenfant (2014) ont étudié l'évolution individuelle de 31 catégories de biens non énergétiques canadiens. Près de la moitié des biens examinés étaient appelés à tirer la reprise des exportations. Depuis, les exportations de biens non énergétiques se sont redressées : dans environ 8 cas sur 10, la croissance observée a été soit plus rapide que celle des variables de référence aux États-Unis, soit du même ordre. Par ailleurs, dans près de la moitié des catégories, la croissance est en train de s'accélérer. De nombreuses catégories de biens non énergétiques très sensibles aux mouvements de change sont à la base du regain constaté, car elles bénéficient de la dépréciation du dollar canadien. Une analyse plus fine révèle que des catégories de produits d'exportation commencent à enregistrer un certain élan ou renouent avec le dynamisme après avoir atteint des niveaux bas. À l'opposé, des catégories de produits sensibles à la fluctuation des prix des matières premières ont été pénalisées par la faiblesse de l'activité et des cours.
Keywords: F10; F14; F43; 330; International topics; Balance of payments and components; Exchange rates; Questions internationals; Balance des paiements et composantes; Taux d'intérêt